The Effect of Immersion Duration in Thyroxine Hormone on Growth of Snakehead Fish Larvae (Channa striata) - Muslim Muslim; Ade Dwi Sasanti; Apriana Apriana (Journal of Aquaculture Science, 2019)
The aim of this research was to determine the best immertion duration to increase growth rate of snakehead fish larva. The research was conducted in Fish Breeding unit Batanghari Sembilan Indralaya, Kabupaten Ogan Ilir. This research used a Completely Randomized Design (CRD), with five treatments (0, 12, 24, 36, and 48 hours of immertion), with three replications. The parameters observed were growth, survival rate and water quality. The results of  this research show that the highest growth rate found in the 24 hours of treatment  with the average value of 0.17 g of weight and increase in length of 1.90 cm. The best survival contained in treatment of immersion for 36 hours with the average value of 71.67%.   Key words: snakehead larvae, thyroxine, growth, immertion